Role of neoadjuvant chemoradiotherapy in liver transplantation for unresectable perihilar cholangiocarcinoma: multicentre, retrospective cohort study. Issue 2 (10th April 2023) - Hoogwater, Frederik J H; Kuipers, Hendrien; de Meijer, Vincent E; Maulat, Charlotte; Muscari, Fabrice; Polak, Wojciech G; van Hoek, Bart; Jézéquel, Caroline; Alwayn, Ian P J; Ijzermans, Jan N M; Mohkam, Kayvan; Mabrut, Jean-Yves; et al.
Abstract: Background: The Mayo protocol for liver transplantation in patients with unresectable perihilar cholangiocarcinoma is based on strict selection and neoadjuvant chemoradiotherapy. The role of neoadjuvant chemoradiotherapy in this scenario remains unclear. The aim of this study was to compare outcomes after transplantation for perihilar cholangiocarcinoma using strict selection criteria, either with or without neoadjuvant chemoradiotherapy. Methods: This was an international, multicentre, retrospective cohort study of patients who underwent transplantation between 2011 and 2020 for unresectable perihilar cholangiocarcinoma using the Mayo selection criteria and receiving neoadjuvant chemoradiotherapy or not receiving neoadjuvant chemoradiotherapy. Endpoints were post-transplant survival, post-transplant morbidity rate, and time to recurrence. Results: Of 49 patients who underwent liver transplantation for perihilar cholangiocarcinoma, 27 received neoadjuvant chemoradiotherapy and 22 did not. Overall 1-, 3-, and 5-year post-transplantation survival rates were 65 per cent, 51 per cent and 41 per cent respectively in the group receiving neoadjuvant chemoradiotherapy and 91 per cent, 68 per cent and 53 per cent respectively in the group not receiving neoadjuvant chemoradiotherapy (1-year hazards ratio (HR) 4.55 (95 per cent c.i. 0.98 to 21.13), P = 0.053; 3-year HR 2.07 (95 per cent c.i. 0.78 to 5.54), P = 0.146; 5-year HR 1.71 (95 per cent c.i. 0.71 to 4.09), P = 0.229). Hepatic vascular complications were more frequent in the group receiving neoadjuvant chemoradiotherapy compared with the group not receiving neoadjuvant chemoradiotherapy (nine of 27 versus two of 22, P = 0.045). In multivariable analysis, tumour recurrence occurred less frequently in the group receiving neoadjuvant chemoradiotherapy (HR 0.30 (95 per cent c.i. 0.09 to 0.97), P = 0.044). Conclusion: In selected patients undergoing liver transplantation for perihilar cholangiocarcinoma, neoadjuvant chemoradiotherapy resulted in a lower risk of tumour recurrence, but was associated with a higher rate of early hepatic vascular complications. Adjustments in neoadjuvant chemoradiotherapy reducing the risk of hepatic vascular complications, such as omitting radiotherapy, may further improve the outcome in patients undergoing liver transplantation for perihilar cholangiocarcinoma. Abstract : This international, multicentre study presents for the first time, to the best of our knowledge, a comparison of two cohorts of patients who underwent transplantation for unresectable perihilar cholangiocarcinoma using the Mayo Clinic selection criteria and either received neoadjuvant chemoradiotherapy or did not receive neoadjuvant chemoradiotherapy. Neoadjuvant chemoradiotherapy resulted in a lower risk of tumour recurrence, but was associated with a higher rate of early hepatic vascular complications. Adjustments in neoadjuvant chemoradiotherapy reducing the risk of hepatic vascular complications may further improve the outcome in patients undergoing liver transplantation for perihilar cholangiocarcinoma.